1993
DOI: 10.1007/bf00277134
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of two genes encoding isoforms of the ATPase involved in sodium efflux in Saccharomyces cerevisiae

Abstract: The ENA2 gene encoding a P-type ATPase involved in Na+ and Li+ effluxes in Saccharomyces cerevisiae has been isolated. The putative protein encoded by ENA2 differs only in thirteen amino acids from the protein encoded by ENA1/PMR2. However, ENA2 has a very low level of expression and for this reason did not confer significant Li+ tolerance on a Li+ sensitive strain. ENA1 and ENA2 are the first two units of a tandem array of four highly homologous genes with probably homologous functions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
170
0
2

Year Published

1995
1995
1998
1998

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 202 publications
(176 citation statements)
references
References 21 publications
4
170
0
2
Order By: Relevance
“…Two genes for P-type ATPase, PMR1 and PMR2, were cloned by Rudolph et al [1] PMR2 was found later to encode a plasma membrane Na+-ATPase responsible for resistance to high concentrations of Na ÷ and Li + [12][13][14]. It was suggested that PMR1 encodes a Ca2+-ATPase.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Two genes for P-type ATPase, PMR1 and PMR2, were cloned by Rudolph et al [1] PMR2 was found later to encode a plasma membrane Na+-ATPase responsible for resistance to high concentrations of Na ÷ and Li + [12][13][14]. It was suggested that PMR1 encodes a Ca2+-ATPase.…”
Section: Discussionmentioning
confidence: 99%
“…]?he cells of the pmrl mutant and the WT strain were harvested from the growth medium, washed 4 times with distilled water and resuspended (2x 108 cells/ml) in buffer-glucose solution containing MES/DMG buffer (25 mM, pH 5.0) and glucose (20 mM [1,4], the isogenic pmr2 mutant cells, lacking a cell-membrane Na+-ATPase [12][13][14] and the isogenic WT cells grew well in YPD medium containing 0.3 mM Ca 2+. The growth rate of the pmrl mutant cells was slightly stimulated by the addition of 20 mM Ca ~+ to the medium, markedly inhibited by reducing external Ca 2+ by EGTA, as previously reported [1,4], but was reduced by only 12% (which is no more than the decrease in the growth rate of the WT cells) by increasing strains.…”
Section: '; Measurements Of Ca 2+ Influxmentioning
confidence: 99%
See 1 more Smart Citation
“…The great number of synthetic changes also implies that the salt-implemented osmotic dehydration instigated impact on many cellular activities. This assumption is strengthened by the fact that genes involved in diverse cellular functions have been reported to be regulated by the osmotic properties of the medium: HAL1, which is involved in Na ϩ -K ϩ selectivity of the cell (20); ENA1, encoding a P-type ATPase participating in the efflux of sodium ions (15); GPD1, which is involved in glycerol production (1,14,41); and TPS2, which encodes one of the subunits of the trehalose synthase complex (20a). Both the maintenance of a proper intracellular Na ϩ balance and the accumulation of the compatible solute glycerol are key features of the osmoregulatory response in yeast cells (7).…”
Section: Discussionmentioning
confidence: 99%
“…Under NaCl stress, the K ϩ uptake system is converted to a high-affinity mode that results in higher K ϩ -Na ϩ discrimination, which reduces the entrance of sodium ions (21). Na ϩ efflux is mediated by the P-type ATPase encoded by ENA1, which is transcriptionally regulated by NaCl (15). These NaClinduced cellular responses involved in ion homeostasis are under the control of a signalling path containing the Ca 2ϩ -calmodulin-dependent protein phosphatase calcineurin (29).…”
mentioning
confidence: 99%